Avaliação do estado epidemiológico e principais fatores relacionados à dinâmica das leishmanioses no município de Lavras, Minas Gerais, Brasil - Narciso, Thiago Pasqua (2019)
Leishmaniasis comprises a set of parasitic diseases caused by Leishmania parasites, especially affecting poor populations in underdeveloped countries and leading each year to thousands of deaths from human visceral leishmaniasis (HVL) and cutaneous deformities due to American tegumentary leishmaniasis (ATL). Visceral leishmaniasis (VL) can also affect domestic dogs (CVL), which are considered the main reservoir of the parasite in the urban environment. Considering the increase in the number of humans and dogs infected with Leishmania, this study aimed to evaluate the epidemiological status and the main factors related to the dynamics of ATL and VL in Lavras, Minas Gerais, Brazil. Systematic and non-systematized collections were performed with CDC and Shannon-type light traps adapted over four years in different quarters of Lavras, allowing the identification of 16 species of sand flies, including Lutzomyia longipalpis, Nyssomiya whitmani, Pintomia fischeri and Evandromyia cortelezzii, suggest the adaptation of these insects to the peridomiciliary environment of the municipality, as well as a possible relationship with the transmission of ATL and VL. In order to better understand the dynamics of VL in Lavras, the first scientific report of HVL was conducted in the city and in the southern region of Minas Gerais. The female patient, 12 years old, had a clinical history of recurrent fever, anorexia, persistent cough and pancytopenia. The diagnosis of HVL was confirmed by using the IT-LEISH® rapid test, as well as PCR positive spinal puncture sample. The treatment was performed with liposomal amphotericin B and the patient showed clinical improvement and complete recovery in about 60 days. The efficacy of the use of meglumine antimoniate for intralesional administration (MA-IL) in a Lavras ATL patient in Lavras diagnosed as positive for Leishmania spp by PCR was also evaluated. The 22-year-old male patient had a history of previous cave travel, and a minor injury appeared after multiple exposure to sand flies. Clinical examination revealed a 2.5 cm diameter itchy ulcer with granular base, raised edges and serous exudate. After treatment with MA-IL, five days after the third session of MA-IL, the lesion was completely epithelized and without local infiltration. The patient had no adverse effects to the drug, demonstrating the safety and efficacy of this form of drug administration in patients with ATL. In order to integrate the different research carried out in the municipality about leishmaniasis, mathematical modeling tools were applied to the phlebotomine fauna data of the municipality, cases of CVL and HVL and secondary data of canine census surveys of the municipality, in which the DPP® screening test and ELISA-EIE were used as confirmatory. Among the main results, the presence of temporal correlation between infected individuals (dogs, humans and sand flies) as well as a stable and low density of sand flies infecting dogs and humans was observed. The information obtained in this work can be very useful for the elaboration and establishment of preventive, therapeutic and control strategies for leishmaniasis in the city and in any region that presents similar conditions, also reinforcing the need for further research in modeling mathematics applied to Neglected Diseases.